2012
DOI: 10.1177/0967010612463488
|View full text |Cite
|
Sign up to set email alerts
|

Of ‘true professionals’ and ‘ethical hero warriors’: A gender-discourse analysis of private military and security companies

Abstract: Private military and security companies (PMSCs) have gained increasingly in importance over the course of the past two decades. Yet, given the intransparency of the industry and the heterogeneity of the companies that comprise it, we thus far know little about the actors involved. In this article, we offer preliminary insights into the self-representation of PMSCs, based on a gender-discourse analysis of the homepages of select companies and their main professional associations. We argue that survival in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Generally, security officers are considered: short-tempered, aggressive, rowdy, law-breaking 'cowboys' (Higate, 2012a(Higate, , 2012b(Higate, , 2011; 'mega-masculine Rambos', 'trigger-happy brutes', 'mercenaries', and 'dogs of war' (Fainaru, 2008;Joachim and Schneiker, 2012); and individuals with a criminal record, predominantly 'motivated by status, salary, joy, and success' (Van Steden et al, 2015: 224). Those images, however, 'ignore the heterogeneity among companies' (Joachim and Schneiker, 2012: 496).…”
Section: Discussion: Hypengyophobia and Placebo Security?mentioning
confidence: 99%
“…Generally, security officers are considered: short-tempered, aggressive, rowdy, law-breaking 'cowboys' (Higate, 2012a(Higate, , 2012b(Higate, , 2011; 'mega-masculine Rambos', 'trigger-happy brutes', 'mercenaries', and 'dogs of war' (Fainaru, 2008;Joachim and Schneiker, 2012); and individuals with a criminal record, predominantly 'motivated by status, salary, joy, and success' (Van Steden et al, 2015: 224). Those images, however, 'ignore the heterogeneity among companies' (Joachim and Schneiker, 2012: 496).…”
Section: Discussion: Hypengyophobia and Placebo Security?mentioning
confidence: 99%
“…Studies within international relations have focused on the implications for state sovereignty and authority (Avant 2004(Avant , 2005Leander 2005Leander , 2013Singer 2003), the role of private security companies in the domains of humanitarian aid (Spearin 2001), how companies engage in identity work and self-framing (Berndtsson 2011;Franke and von Boemcken 2011;Joachim and Schneiker 2012a), and the role of gender discourses and masculinities (Higate 2012;Joachim and Schneiker 2012b). In the fi eld of international (humanitarian) law, scholars have addressed the legal frameworks in which such companies can and cannot operate (Boghosian 2005;Joh 2005;Zarate 1998;Kinsey 2005;Schreier and Caparani 2005;Th orburn 2010) and the crucial role that national and international regulation plays in determining such legal parameters (Berg 2003;Cockayne 2008;Sarre and Prenzler 1999).…”
Section: Erella Grassiani and Tessa Diphoornmentioning
confidence: 99%
“…Critical masculinity studies have been an important influence in this research field. By examining the gendered practices of contractors on the ground (Chisholm, 2010(Chisholm, , 2014bHigate, 2012) as well as PMSCs' marketing strategies (Joachim & Schneiker, 2012, it was shown that the industry is not just a masculinised space but (re)produces a variety of hierarchically positioned masculinities.…”
Section: Introductionmentioning
confidence: 99%